Characterization and storage stability of spray dried soy-rapeseed lecithin/ trehalose liposomes loaded with a tilapia viscera hydrolysate (2021)
ABSTRACT: Drying-induced stabilization is a challenge that delivery systems still face. This study aims to investigate the effects of adding trehalose to spray dried soy-rapeseed lecithin liposomes, and the storage stability of the dried liposomes loaded with a tilapia viscera protein hydrolysate, during 42 days at 4 ◦C and 23 ◦C, and at different relative humidity (RH). Particle size increased from 215 to 250 nm in fresh liposomes to 258–314 nm after spray drying according to trehalose concentration, all preparations showing a strong electronegative ζ Potential (− 48.5 to − 59.9 mV). Dried liposomes stored at 4 ◦C maintained lower polydispersity and higher solubility than those stored at 23 ◦C. Changes in water activity (Aw), FTIR and DSC revealed structural changes in samples stored at 23 ◦C and high RH. Spray dried hydrolysate-containing liposomes could be considered as a functional food ingredient due to the substantial antioxidant activity and angiotensin-converting enzyme (ACE) inhibitory capacity after in vitro simulated gastrointestinal digestion. Industrial relevance: The availability of a natural liposomal preparation in dry powder form, capable to maintain its bioactive properties, is a great advantage for the functional food industry, since it favours the stability, transport and storage of the ingredient prior to use, and allows great versatility to be incorporated in solid restructured products.